STUDENT’S LEARNING STYLES IN LEARNING READING COMPREHENSION - Sinta sasmita; Siti Aisah Ginting (Universitas Negeri Medan, 2017)
This study is about student’s learning styles in learning reading comprehension. The design of this research was descriptive research. The data were collected by using questionnaires and observation sheet. The subject of the study are the XI AP 2 of SMK Swasta Harapan Stabat and the object of the study are the students learning styles in learning reading comprehension. The data were analyzed by using Fleming theory. The purpose of conducting this research was find out whether the most dominant learning style in reading comprehension and to find out what are the types of student’s learning styles which has higher achievement in reading comprehension of XI grade in SMK Swasta Harapan Stabat in academic 2016/2017. There were 32 students as the subject of this research. In this case, the researcher collected the data by using learning style questionnaire and observation. The result showed that auditory learning style is the most dominant learning style at the tenth grade students at SMK Swasta Harapan Stabat, the percentage was 71,87%, it means 23 from 32 students prefer to hear than read and move. The second was kinesthetic learning style, the score, 21,88%, means that only 7 students prefer to move. Then, visual learning style, score 6,25%, means that 2 from 32 students prefer to read. For the fastest student’s in reading comprehension came from auditory students or auditory learners. They get score 69,56% followed kinesthetic 21,74%, and visual 8,70%.